Procesos decisorios y comportamiento de los electores bogotanos en contiendas locales (2008)
This research studies citizen decisions in a local election, grouping voters according to vote motivations, candidate attributes and decision inputs. We suggest that voter motivation may be more determined by externaland marketing influences than internal motivations. In addition, we believethat voters consider candidate attributes more than his or her political proposal. Since the voters’ decision is based on very little information about all possible alternatives, it is biased in favor of the strongest campaign.